Application of Computer Virtual Reality Technology in College Sports Training. Issue 2 (October 2020) - Liang, Cheng
Abstract: With the continuous development of social science and technology, the application of computers is more and more extensive. The application of computer "virtual reality" (hereinafter referred to as VR) technology in college physical education (hereinafter referred to as PE) training can enrich the content of PE classroom teaching, update classroom teaching methods, and improve the quality and efficiency of PE training teaching. However, in the process of practical application, there are still some problems to be solved.